THEORETICAL STUDY OF THE EFFECTS OF ELECTRON-WITHDRAWING AND -DONATING GROUP ON THE LUMINESCENT PROPERTIES OF EUROPIUM COMPLEXES WITH SUBSTITUTED 1,10 PHENANTHROLINE - (NIM : 20510030); Pembimbing : Dr. M. Abdulkadir Martoprawiro, SUDARLIN
The ability of electron-withdrawing and -donating group (EDG/ EWG) affects the electron distribution of a molecule is the background of this research. If a molecule which have different electron distribution is used as ligand on a metal, the structure and excitated energy of the complexes is be different and the luminescent properties is be variated. The varition of the luminescent properties have been studied theoritically on the [Eu(III)(1,10-phenanthroline)]3+ complexes using CH3, CH=CH2, F, OH, CN, CF3, NO2, and CHO group to get spesific conclusion about effects of the group. The parameters studied are energy difference between singlet and triplet excited state of the ligan Delta EISC), difference between the triplet excited state energy of the ligan and the emission energy of the Eu (III) for 5D0 level (deltaEET), and energy transfer rate (WET) between ligan and europium. The parameters were studied theoritically using DFT/B3LYP method for the ground state of the molecules and TDDFT method for excited states of the molecules. 6-31G basis set was used for the ligand atoms and Stuttgart RSC 1997 ECP for europium atom. EDG and EWG were varied as 2-X-1,10-phenanthroline, 5-X-1,10-phenanthroline, and random-X-1,10- phenanthroline. The results show that the value of Delta EISC is greater when using EDG (CH3, CH=CH2, F, and OH) and smaller when using EWG (CN, CF3, NO2, and CHO). Different pattern occurs in the value of DeltaEET, which greater when using a group that has no double bond (CH3, F, OH, and CF3) and smaller when using a group that has a double bond (CH=CH2, CN, NO2, and CHO). The pattern was consistent in the position of 2-X-1,10- phenanthroline, 5-X-1,10-phenanthroline, and random-X-1,10-phenanthroline. The highest value of WET was obtained when using ligand 2-NO2-1,10-phenanthroline which is caused by a direct interaction between the atom of the group with europium atom. Therefore, it can be concluded that the type, propeties, position, and variation of the EDG/ EWG affects the DeltaEISC, DeltaEET, and WET of the [Eu(III)(1,10-phenanthroline)]3+ complexes. Specifically, EDG increases the DeltaEISC value, the group which have (pi) bonding decrease the DeltaEET value, and the group which can be interacted with europium as ion center increases the WET value. The result of this study is hoped to be a guide to design europium complexes which have better luminecent properties.